2008
DOI: 10.1111/j.1440-1681.2008.04976.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF INHIBITION OF NEURONAL NITRIC OXIDE SYNTHASE AND l‐ARGININE SUPPLEMENTATION ON RENAL ISCHAEMIA–REPERFUSION INJURY AND THE RENAL NITRIC OXIDE SYSTEM

Abstract: The role of nitric oxide synthases (NOS) and the nitric oxide (NO) substrate l-arginine in renal ischaemia-reperfusion (I/R) has been studied extensively. However, the results reported are often controversial. In the present study, we examined the effects of the neuronal (n) NOS inhibitor 7-nitroindazole (7-NI) and L-arginine administration on renal I/R injury and the renal NO system in rats. Following 7 days pretreatment with 7-NI (50 mg/kg per day), L-arginine (2 g/kg per day) or vehicle (dimethylsulphoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
9
0
2
Order By: Relevance
“…35 Ischemia decreases L-ARG concentrations in the renal cortex and medulla, resulting in a decreased substrate supply for NO synthesis. This situation can be reversed by exogenous supplementation of L-ARG, 38 as was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…35 Ischemia decreases L-ARG concentrations in the renal cortex and medulla, resulting in a decreased substrate supply for NO synthesis. This situation can be reversed by exogenous supplementation of L-ARG, 38 as was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 60%
“…35 We found that exogenous administration of L-ARG for 21 days increased the expression of eNOS, nNOS and iNOS. Rusai et al 38 showed that, in kidneys that underwent ischemia, supplementation with L-ARG for 7 days increased the expression of mRNA for the three isoforms of NOS. Intrarenal NO production stimulated by L-ARG also increases renal sodium excretion by a direct tubular action and by regulating vascular tone in the pressure natriuretic response in the renal medulla.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a more recent study by Rusai et al in the ischemic rat kidney, observed that L-arginine (2 g/kg body weight daily) didn't affect the injury sustained from I/R, but did increase the mRNA expression of NOS isoforms. This may be explained by time and dose administration differences between studies, along with the severity of the ischemic injury [90]. Again, more studies examining the ideal dose and time of administration of L-arginine will be helpful in determining its possible therapeutic value.…”
Section: Endogenous No: L-argininementioning
confidence: 95%
“…Data regarding the impact of L-Arg on the regulation of the expression of genes and proteins for all NOS isoforms are scarce. Rusai et al have demonstrated that L-Arg supplementation for seven days in rats with a model of renal ischemia increased the mRNA expression of all three NOS isoforms, but increased only NOS II protein levels [40].…”
Section: Discussionmentioning
confidence: 99%